Binder resin composition for toner

JP7631134B2Active Publication Date: 2025-02-18KAO CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021117186
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-15
Publication Date
2025-02-18
Estimated Expiration
2041-07-15

AI Technical Summary

Benefits of technology

【0008】 本発明のトナー用結着樹脂組成物は画像の耐擦過性と光沢性に優れ、また、良好な粉砕性を有するという優れた効果を奏するものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631134000001
    Figure 0007631134000001
  • Figure 0007631134000002
    Figure 0007631134000002
  • Figure 0007631134000003
    Figure 0007631134000003
Patent Text Reader

Abstract

To provide a binder resin composition for a toner which is excellent in scratch resistance and glossiness of an image, and has good crushability, and a toner for electrostatic charge image development containing the binder resin composition.SOLUTION: There are provided a binder resin composition for a toner that contains a crystalline polyester resin and an amorphous polyester resin, wherein the crystalline polyester resin is a polycondensate of a raw material monomer containing ethylene glycol, an aliphatic dicarboxylic acid-based compound having 12 or more and 16 or less carbon atoms, and an aliphatic monocarboxylic acid-based compound having 16 or more and 24 or less carbon atoms, and a content of the aliphatic monocarboxylic acid-based compound is 7 mol% or more and 20 mol% or less in the raw material monomer; and a toner for electrostatic charge image development which contains the binder resin composition for the toner and a coloring agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a binder resin composition for a toner used for developing a latent image formed in, for example, an electrophotographic method, an electrostatic recording method, an electrostatic printing method, etc., and a toner for developing an electrostatic image containing the binder resin composition. [Background technology]

[0002] Patent Document 1 discloses a binder resin composition for toners, which contains an amorphous polyester A and a crystalline polyester C, in which the amorphous polyester A is an amorphous polyester obtained by polycondensing an alcohol component containing an aromatic diol and an aliphatic diol having 3 to 6 carbon atoms and a carboxylic acid component, and the crystalline polyester C is a crystalline polyester obtained by polycondensing an alcohol component containing an aliphatic diol having 2 to 9 carbon atoms and a carboxylic acid component.

[0003] Patent Document 2 discloses a toner for developing electrostatic images, which contains an amorphous polyester resin and a crystalline polyester resin, the amorphous polyester resin being a polycondensate of an alcohol component (A-al) and a carboxylic acid component (A-ac) containing succinic acid or an anhydride thereof substituted with a linear aliphatic hydrocarbon group having from 16 to 18 carbon atoms, and the crystalline polyester resin being a polycondensate of an alcohol component (C-al) and a carboxylic acid component (C-ac), the alcohol component (C-al) containing a monoalcohol having from 6 to 24 carbon atoms, and the carboxylic acid component (C-ac) containing at least one selected from the group consisting of a monocarboxylic acid having from 6 to 24 carbon atoms. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-90628 A [Patent Document 2] JP 2020-60687 A Summary of the Invention [Problem to be solved by the invention]

[0005] Since crystalline polyester resin has a crystalline structure, it has high slipperiness and is expected to improve abrasion resistance, but when it is mixed with amorphous polyester resin as a binder resin for toner, if the compatibility between them is too high, the crystalline polyester resin in the printed matter will become amorphized, and the expected slipperiness will not be exhibited. In addition, the amorphized crystalline portion will have a soft and flexible structure, which will reduce the grindability of the toner. On the other hand, if the compatibility is low, the crystalline polyester resin will maintain its crystallinity even in the amorphous polyester resin, so the abrasion resistance and grindability will be good, but the refractive index difference between the crystalline structure portion and the amorphous portion will be large, which will reduce the gloss of the resulting printed matter.

[0006] The present invention relates to a binder resin composition for a toner which provides an image with excellent abrasion resistance and gloss and also has good grindability, and to a toner for developing an electrostatic image which contains the binder resin composition. [Means for solving the problem]

[0007] The present invention relates to [1] A binder resin composition for toners, which contains a crystalline polyester resin and an amorphous polyester resin, the crystalline polyester resin being a polycondensate of raw material monomers including ethylene glycol, an aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms, and an aliphatic monocarboxylic acid compound having 16 to 24 carbon atoms, and the content of the aliphatic monocarboxylic acid compound in the raw material monomers is 7 mol % to 20 mol %; and [2] A toner for developing electrostatic images, comprising the binder resin composition for toners according to [1] above and a colorant. Regarding. Effect of the Invention

[0008] The binder resin composition for toner of the present invention exhibits excellent effects such as excellent abrasion resistance and gloss of an image and good grindability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The binder resin composition for toner of the present invention is a polycondensate of raw material monomers including ethylene glycol, a long-chain aliphatic dicarboxylic acid compound, and a long-chain aliphatic monocarboxylic acid compound, and although the details are unknown, it is presumed that the effects of the present invention are achieved by the interaction of these raw material monomers. By using ethylene glycol as a raw material monomer, two adjacent ester groups can be arranged in the crystalline polyester resin, which not only increases the cohesive strength and facilitates crystal growth, but also promotes the formation of crystal nuclei due to the low polarity long-chain aliphatic dicarboxylic acid-derived portion and the long-chain aliphatic monocarboxylic acid arranged at the end. This allows the crystalline polyester resin to be quickly recrystallized after fixing, resulting in the expression of the slipperiness derived from the crystals in the printed matter and good abrasion resistance. In addition, by quickly generating crystal nuclei, the crystal size does not increase and the crystal domains remain finely dispersed, resulting in an increased number of interfaces between the crystalline polyester resin and amorphous polyester resin portions. The resin breaks at these interfaces, improving grindability. In addition, because the crystalline polyester resin is finely dispersed, the effect on the refractive index of the amorphous portions is suppressed, and the gloss of the resulting image is not impaired.

[0010] As described above, the crystalline polyester resin is a polycondensation product of raw material monomers including ethylene glycol, a long-chain aliphatic dicarboxylic acid compound, and a long-chain aliphatic monocarboxylic acid compound.

[0011] The content of ethylene glycol in the diol is preferably 80 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, even more preferably 98 mol % or more, and even more preferably 100 mol %.

[0012] Examples of other diols include aliphatic diols other than ethylene glycol, such as 1,4-butanediol, 1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, and 1,14-tetradecanediol, and aromatic diols, such as alkylene oxide adducts of bisphenol A.

[0013] The content of the diol in the raw material monomers is preferably 20 mol% or more, more preferably 25 mol% or more, even more preferably 30 mol% or more, even more preferably 35 mol% or more, and is preferably 60 mol% or less, more preferably 55 mol% or less, even more preferably 50 mol% or less.

[0014] From the viewpoints of abrasion resistance, pulverizability and gloss, the carbon number of the long-chain aliphatic dicarboxylic acid compound is 12 or more, and preferably 14 or more, and from the viewpoints of abrasion resistance, gloss and low-temperature fixability, it is 16 or less. Here, when the aliphatic monocarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0015] Examples of long-chain aliphatic dicarboxylic acid compounds include dodecanedioic acid (number of carbon atoms: 12), tetradecanedioic acid (number of carbon atoms: 14), hexadecanedioic acid (number of carbon atoms: 16), succinic acid having an alkyl or alkenyl group on the side chain, anhydrides of these acids, and alkyl esters in which the alkyl group has 1 to 3 carbon atoms. Of these, dodecanedioic acid and / or tetradecanedioic acid are preferred.

[0016] The content of the long-chain aliphatic dicarboxylic acid compound in the dicarboxylic acid compounds is preferably 80 mol % or more, more preferably 90 mol % or more, even more preferably 95 mol % or more, even more preferably 98 mol % or more, and even more preferably 100 mol %.

[0017] Examples of other dicarboxylic acid compounds include aliphatic dicarboxylic acid compounds other than the long-chain aliphatic dicarboxylic acid compounds, such as succinic acid (carbon number: 4), fumaric acid (carbon number: 4), adipic acid (carbon number: 6), suberic acid (carbon number: 8), azelaic acid (carbon number: 9), and sebacic acid (carbon number: 10), as well as aromatic dicarboxylic acid compounds, such as phthalic acid, isophthalic acid, and terephthalic acid, as well as anhydrides of these acids and alkyl esters in which the alkyl group has 1 to 3 carbon atoms.

[0018] The content of the dicarboxylic acid compound in the raw material monomer is preferably 10 mol % or more, more preferably 15 mol % or more, even more preferably 20 mol % or more, and preferably 60 mol % or less, more preferably 50 mol % or less, even more preferably 40 mol % or less.

[0019] From the viewpoints of abrasion resistance, grindability and gloss, the carbon number of the long-chain aliphatic monocarboxylic acid compound is 16 or more, preferably 18 or more, more preferably 20 or more, and from the viewpoints of abrasion resistance, gloss and low-temperature fixability, the carbon number is 24 or less, preferably 22 or less. Here, when the long-chain aliphatic monocarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.

[0020] Examples of long-chain aliphatic monocarboxylic acid compounds include aliphatic monocarboxylic acids such as palmitic acid, stearic acid, and behenic acid, and alkyl esters of these acids in which the alkyl group has 1 to 3 carbon atoms. Of these, stearic acid and / or behenic acid are preferred.

[0021] The content of the long-chain aliphatic monocarboxylic acid compound in the raw material monomer is 7 mol % or more, preferably 9 mol % or more, more preferably 11 mol % or more, from the viewpoints of abrasion resistance, grindability and gloss, and is preferably 20 mol % or less, preferably 17 mol % or less, more preferably 15 mol % or less, from the viewpoints of abrasion resistance, gloss and low-temperature fixability.

[0022] The raw material monomers may include aliphatic monocarboxylic acid compounds other than the long-chain aliphatic monocarboxylic acid compounds such as capric acid, lauric acid, and myristic acid, aliphatic monoalcohols, and trivalent or higher monomers (trivalent or higher alcohols and / or trivalent or higher carboxylic acid compounds).

[0023] The crystalline polyester resin can be produced, for example, by polycondensing raw material monomers containing an alcohol and a carboxylic acid compound in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature of preferably 130°C or higher, more preferably 170°C or higher, and preferably 250°C or lower, more preferably 240°C or lower.

[0024] The esterification catalyst includes tin compounds and titanium compounds, and in the present invention, from the viewpoints of image heat resistance and charging stability, tin compounds are preferred.

[0025] As the tin compound, a tin(II) compound having no Sn-C bond is preferred.

[0026] As the tin(II) compound having no Sn-C bond, a tin(II) compound having no Sn-C bond but an Sn-O bond, a tin(II) compound having an Sn-X (X represents a halogen atom) bond, etc. are preferred, and a tin(II) compound having an Sn-O bond is more preferred.

[0027] Examples of tin(II) compounds having an Sn-O bond include tin(II) oxalate, tin(II) acetate, tin(II) octanoate, tin(II) 2-ethylhexanoate, tin(II) laurate, tin(II) stearate, tin(II) oleate, and other tin(II) carboxylates having a carboxylic acid group having 2 to 28 carbon atoms; alkoxytin(II) having an alkoxy group having 2 to 28 carbon atoms, such as octyloxytin(II), lauroxytin(II), stearoxytin(II), and oleyloxytin(II); tin(II) oxide; and tin(II) sulfate. Examples of tin(II) compounds having an Sn-X (X represents a halogen atom) bond include tin(II) halides such as tin(II) chloride and tin(II) bromide. Among these, the following tin(II) halides are particularly preferred from the viewpoint of catalytic activity: (R 1 COO)2Sn (where R 1 represents an alkyl or alkenyl group having 5 to 19 carbon atoms), 2 O)2Sn(where R 2 represents an alkyl or alkenyl group having 6 to 20 carbon atoms), or tin(II) oxide represented by SnO, 1 Tin(II) fatty acid or tin(II) oxide represented by (COO)2Sn is more preferred, and tin(II) octanoate, tin(II) 2-ethylhexanoate, tin(II) stearate or tin(II) oxide is even more preferred.

[0028] The amount of the esterification catalyst, preferably a tin compound, used is preferably 0.01 part by mass or more, more preferably 0.1 part by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, per 100 parts by mass of the raw material monomer.

[0029] An example of the esterification promoter is gallic acid. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, relative to 100 parts by mass of the raw material monomer. An example of the polymerization inhibitor is tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, relative to 100 parts by mass of the raw material monomer.

[0030] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.

[0031] From the viewpoint of storage stability, the softening point of the crystalline polyester resin is preferably 50°C or higher, more preferably 60°C or higher, even more preferably 65°C or higher, and even more preferably 75°C or higher, and from the viewpoint of low-temperature fixability, it is preferably 100°C or lower, more preferably 90°C or lower.

[0032] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, i.e., the value of [softening point / maximum endothermic peak temperature]. A crystalline resin is a resin having a crystallinity index of 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. On the other hand, an amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the crystallinity index is greater than 1.4, preferably greater than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.

[0033] From the viewpoint of storage stability, the melting point of the crystalline polyester resin is preferably 50°C or higher, more preferably 60°C or higher, even more preferably 65°C or higher, and even more preferably 75°C or higher, and from the viewpoint of low-temperature fixability, it is preferably 100°C or lower, more preferably 90°C or lower.

[0034] From the viewpoint of controlling crystallization, it is preferable to control the acid value of the crystalline polyester resin low, preferably 10 mgKOH / g or less, more preferably 8 mgKOH / g or less, even more preferably 6 mgKOH / g or less, and preferably 1 mgKOH / g or more.

[0035] From the viewpoint of controlling crystallization, it is preferable to control the hydroxyl value of the crystalline polyester resin to a low value, preferably 10 mgKOH / g or less, more preferably 8 mgKOH / g or less, even more preferably 6 mgKOH / g or less, and preferably 1 mgKOH / g or more.

[0036] From the viewpoint of controlling crystallization, it is preferable to control the sum of the acid value and the hydroxyl value of the crystalline polyester resin low, preferably 15 mgKOH / g or less, more preferably 12 mgKOH / g or less, even more preferably 9 mgKOH / g or less, and preferably 2 mgKOH / g or more.

[0037] The weight average molecular weight of the crystalline polyester resin is preferably 5,000 or more, more preferably 6,000 or more, and even more preferably 7,000 or more from the viewpoint of storage stability, and is preferably 12,000 or less, more preferably 10,000 or less, and even more preferably 9,000 or less from the viewpoint of controlling crystallization.

[0038] The molecular weight of the polyester resin can be adjusted by the amount of monovalent long-chain aliphatic monomer used and the amount of trivalent or higher raw monomer (trivalent or higher carboxylic acid compound and trivalent or higher alcohol) used.

[0039] The content of the crystalline polyester resin in the binder resin composition is preferably 2% by mass or more, more preferably 5% by mass or more, even more preferably 8% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less.

[0040] The amorphous polyester resin is preferably a polycondensate of an alcohol component containing an alkylene oxide adduct of bisphenol A and a carboxylic acid component containing an aromatic dicarboxylic acid compound.

[0041] Examples of the alkylene oxide adduct of bisphenol A include those represented by the formula (I):

[0042] [ka]

[0043] (In the formula, OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y are the average number of moles of alkylene oxide added, each of which is a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less.) From the viewpoint of grindability, a propylene oxide adduct of bisphenol A is more preferred.

[0044] The content of the propylene oxide adduct of bisphenol A in the alcohol component is preferably 30 mol% or more, more preferably 45 mol% or more, even more preferably 70 mol% or more, even more preferably 85 mol% or more, and is 100 mol% or less, preferably 98 mol% or less, more preferably 97 mol% or less.

[0045] From the viewpoint of low-temperature fixing ability, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, even more preferably 95 mol % or more, and even more preferably 100 mol %.

[0046] Examples of other alcohol components include aliphatic diols, bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trimethylolpropane and other trihydric or higher alcohols.

[0047] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0048] From the viewpoint of charging stability, the content of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 10 mol % or more, more preferably 25 mol % or more, and even more preferably 40 mol % or more, and when the carboxylic acid component contains other carboxylic compounds, it is preferably 100 mol % or less, more preferably 95 mol % or less.

[0049] Examples of the other carboxylic acid component include an aliphatic dicarboxylic acid compound and a tri- or higher carboxylic acid compound. From the viewpoint of increasing the softening point, it is preferable to contain a tri- or higher carboxylic acid compound.

[0050] Examples of the trivalent or higher carboxylic acid compound include trimellitic acid, pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.

[0051] From the viewpoint of increasing the softening point, the content of the trivalent or higher carboxylic acid compound in the carboxylic acid component is preferably 3 mol % or more, more preferably 5 mol % or more, and even more preferably 8 mol % or more, and is preferably 35 mol % or less, more preferably 25 mol % or less.

[0052] From the viewpoint of adjusting the molecular weight and softening point of the polyester resin, the alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.

[0053] From the viewpoint of adjusting the softening point of the polyester resin, the equivalent ratio of the carboxylic acid component to the alcohol component (COOH group / OH group) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.75 or more, and is preferably 1.2 or less, more preferably 1.15 or less.

[0054] The amorphous polyester resin can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature of preferably 130°C or higher, more preferably 170°C or higher, and preferably 250°C or lower, more preferably 240°C or lower.

[0055] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropylate bistriethanolamine, and tin compounds are preferred. The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, relative to 100 parts by mass of the raw material monomer. Examples of the esterification promoter include gallic acid, etc. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, relative to 100 parts by mass of the raw material monomer. Examples of the polymerization inhibitor include tert-butylcatechol, etc. The amount of the polymerization inhibitor used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, relative to 100 parts by mass of the raw material monomer.

[0056] The amorphous polyester resin preferably contains an amorphous polyester resin AL having a weight average molecular weight of 4,000 or more and 10,000 or less.

[0057] The weight average molecular weight of the amorphous polyester resin AL is 4,000 or more, preferably 4,500 or more, and more preferably 5,000 or more, from the viewpoints of abrasion resistance and electrostatic stability, and is 10,000 or less, preferably 8,000 or less, and more preferably 7,000 or less, from the viewpoints of abrasion resistance, pulverizability, and gloss.

[0058] From the viewpoint of storage stability, the softening point of the amorphous polyester resin AL is preferably 70°C or higher, more preferably 90°C or higher, and even more preferably 95°C or higher, and from the viewpoint of low-temperature fixability, it is preferably 130°C or lower, more preferably 125°C or lower, and even more preferably 120°C or lower.

[0059] The glass transition temperature of the amorphous polyester resin AL is preferably 40° C. or higher, more preferably 45° C. or higher, and even more preferably 50° C. or higher, from the viewpoint of electrostatic stability, and is preferably 70° C. or lower, more preferably 65° C. or lower, and even more preferably 60° C. or lower, from the viewpoint of controlling crystallization.

[0060] From the viewpoint of controlling crystallization, the acid value of the amorphous polyester resin AL is preferably 10 mgKOH / g or less, more preferably 8 mgKOH / g or less, further preferably 5 mgKOH / g or less, and preferably 1 mgKOH / g or more.

[0061] From the viewpoint of controlling the compatibility with the crystalline polyester resin, the hydroxyl value of the amorphous polyester resin AL is preferably 50 mgKOH / g or less, and more preferably 45 mgKOH / g or less.

[0062] The content of the amorphous polyester resin AL in the binder resin composition is preferably 40% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, and is preferably 70% by mass or less, more preferably 65% ​​by mass or less, even more preferably 60% by mass or less.

[0063] The amorphous polyester resin may further contain an amorphous polyester resin AH having a weight average molecular weight higher than that of the amorphous polyester resin AL.

[0064] The weight average molecular weight of the amorphous polyester resin AH is preferably 30,000 or more, more preferably 50,000 or more, and even more preferably 60,000 or more, from the viewpoint of hot offset resistance, and is preferably 150,000 or less, more preferably 120,000 or less, and even more preferably 100,000 or less, from the viewpoint of low-temperature fixability.

[0065] The softening point of the amorphous polyester resin AH is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher, from the viewpoint of fixing width, and is preferably 180°C or lower, more preferably 160°C or lower, and even more preferably 150°C or lower, from the viewpoint of low-temperature fixing ability.

[0066] The glass transition temperature of the amorphous polyester resin AH is preferably 40° C. or higher, more preferably 45° C. or higher, and even more preferably 50° C. or higher, from the viewpoint of electrostatic charge stability, and is preferably 70° C. or lower, more preferably 65° C. or lower, and even more preferably 60° C. or lower, from the viewpoint of controlling crystallization.

[0067] From the viewpoint of controlling crystallization, the acid value of the amorphous polyester resin AH is preferably 30 mgKOH / g or less, more preferably 25 mgKOH / g or less, further preferably 20 mgKOH / g or less, and preferably 10 mgKOH / g or more.

[0068] From the viewpoint of controlling the compatibility with the crystalline polyester resin, the hydroxyl value of the amorphous polyester resin AH is preferably 35 mgKOH / g or less, more preferably 30 mgKOH / g or less, and is preferably 15 mgKOH / g or more, more preferably 20 mgKOH / g or more.

[0069] The content of the amorphous polyester resin AH in the binder resin composition is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less.

[0070] The total content of the amorphous polyester resin in the binder resin composition is preferably 80% by mass or more, more preferably 85% by mass or more, and preferably 98% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less.

[0071] The mass ratio of the crystalline polyester resin to the amorphous polyester resin (crystalline polyester resin / amorphous polyester resin) is preferably 2 / 98 or more, more preferably 5 / 95 or more, and even more preferably 8 / 92 or more, from the viewpoint of abrasion resistance and image density, and is preferably 20 / 80 or less, more preferably 15 / 85 or less, from the viewpoint of charging stability.

[0072] The binder resin composition may contain a resin other than the crystalline polyester resin and the amorphous polyester resin within a range that does not impair the effects of the present invention. Examples of the other resin include polyester resins other than the crystalline polyester resin and the amorphous polyester resin, vinyl resins such as styrene-acrylic resin, epoxy resin, polycarbonate, polyurethane, and composite resins containing two or more of these resins.

[0073] The total content of the crystalline polyester resin and the amorphous polyester resin in the binder resin composition is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, even more preferably 98% by mass or more, and even more preferably 100% by mass.

[0074] Further, the present invention provides a toner containing the binder resin composition for toner of the present invention as a binder resin, specifically, a toner for developing electrostatic images containing the binder resin composition for toner of the present invention and a colorant.

[0075] The content of the binder resin composition in the toner is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, even more preferably 80% by mass or more, and is preferably less than 100% by mass, more preferably 98% by mass or less, even more preferably 95% by mass or less.

[0076] As the colorant, dyes, pigments, magnetic materials, etc., which are used as colorants for toners, can be used. In the present invention, the toner may be either a black toner or a color toner.

[0077] In the present invention, the colorant is preferably a hydrophobic pigment, since the effect of improving the image density by improving the dispersibility of the colorant is more significant. Examples of the hydrophobic pigment include phthalocyanine pigments, quinacridone pigments, isoindolinone pigments, naphthol pigments, and lake pigments, and among these, phthalocyanine pigments, quinacridone pigments, and naphthol pigments are preferred, phthalocyanine pigments are more preferred, and copper phthalocyanine pigments such as CI Pigment Blue 15:3 are even more preferred.

[0078] From the viewpoint of improving the image density and low-temperature fixability of the toner, the content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and is preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin composition.

[0079] The toner for developing electrostatic images of the present invention may contain additives such as a release agent, a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, and a cleaning property improver, in addition to the binder resin composition and the colorant, and it is preferable that the toner contains a release agent and a charge control agent.

[0080] Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.

[0081] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of toner transferability, and is preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower, from the viewpoint of low-temperature fixability.

[0082] The content of the release agent is preferably 1 part by mass or more and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and further preferably 3 parts by mass or less, relative to 100 parts by mass of the binder resin composition, from the viewpoints of low-temperature fixability and offset resistance of the toner and dispersibility in the binder resin composition.

[0083] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.

[0084] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Kasei Corporation); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.).

[0085] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizenspiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (Clariant), nitroimidazole derivatives, and organometallic compounds.

[0086] From the viewpoint of the charging stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the binder resin composition.

[0087] The toner of the present invention may be a toner obtained by any of the conventionally known methods such as a melt kneading method, an emulsion phase inversion method, a polymerization method, etc., but from the viewpoint of productivity and dispersibility of the colorant, a pulverized toner by a melt kneading method is preferred. In the case of a pulverized toner by a melt kneading method, for example, raw materials such as a binder resin (binder resin composition), a colorant, and, if necessary, a release agent and a charge control agent are uniformly mixed in a mixer such as a Henschel mixer, and then melt kneaded in an internal kneader, a single-screw or twin-screw extruder, an open roll type kneader, etc., and cooled, pulverized, and classified to produce the toner.

[0088] In the production of the toner, a binder resin composition in which a crystalline polyester resin and an amorphous polyester resin are mixed in advance may be used, but in the production of the toner, these resins may be directly used for mixing the raw materials.

[0089] In the toner of the present invention, it is preferable to use an external additive in order to improve transferability.The external additive includes inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, zinc oxide, etc., and organic fine particles such as resin particles such as melamine resin fine particles and polytetrafluoroethylene resin fine particles, and two or more kinds may be used in combination.Among these, silica is preferable, and from the viewpoint of transferability of the toner, hydrophobic silica that has been hydrophobized is more preferable.

[0090] Examples of hydrophobic treatment agents for hydrophobizing the surfaces of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), silicone oil, octyltriethoxysilane (OTES), and methyltriethoxysilane.

[0091] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.

[0092] From the viewpoint of the electrostatic chargeability, fluidity, and transferability of the toner, the content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner before being treated with the external additive, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.

[0093] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50 ) refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is regarded as the volume median particle size of the toner.

[0094] The toner of the present invention can be used as it is as a toner for one-component development, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a one-component development system or a two-component development system, respectively. EXAMPLES

[0095] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.

[0096] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.

[0097] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan, Inc.), weigh 0.01 to 0.02 g of sample into an aluminum pan, cool the sample from room temperature (20°C) to 0°C at a rate of 10°C / min, and maintain the sample at that temperature for 1 minute. Then, measure the endothermic peak while increasing the temperature to 180°C at a rate of 10°C / min. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature.

[0098] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated from room temperature (20°C) to 200°C at a heating rate of 10°C / min, and cooled from that temperature to 0°C at a heating rate of 10°C / min. Next, the sample is heated to 180°C at a heating rate of 10°C / min, and the endothermic peak is measured. The temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak is taken as the glass transition temperature.

[0099] [Acid value and hydroxyl value of crystalline polyester resin] Measure based on the method of JIS K0070:1992, except that the measurement solvent is changed from the mixed solvent of ethanol and ether specified in JIS K0070:1992 to tetrahydrofuran.

[0100] [Acid value of amorphous polyester resin] Measure based on the method of JIS K0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K0070:1992 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)).

[0101] [Hydroxyl value of amorphous polyester resin] Measure based on the method of JIS K0070:1992, except that the measurement solvent is changed from the mixed solvent of ethanol and ether specified in JIS K0070:1992 to tetrahydrofuran.

[0102] [Weight average molecular weight of resin] The weight average molecular weight is determined by gel permeation chromatography (GPC) according to the following method. (1) Preparation of sample solution The sample is dissolved in tetrahydrofuran (amorphous resin) or chloroform (crystalline resin) at 40° C. so that the concentration becomes 0.5 g / 100 mL. Next, this solution is filtered using a PTFE type membrane filter "DISMIC-25JP" (manufactured by Toyo Roshi Kaisha, Ltd.) with a pore size of 0.20 μm to remove insoluble components, and the sample solution is obtained. (2) Molecular weight measurement The following measuring equipment and analytical column are used, and tetrahydrofuran (amorphous resin) or chloroform (crystalline resin) is passed as the eluent at a flow rate of 1 mL per minute. The column is stabilized in a thermostatic bath at 40°C. 100 μL of the sample solution is injected into the column for measurement. The molecular weight of the sample is calculated based on a calibration curve that has been prepared in advance. The calibration curve used here is a series of monodisperse polystyrenes (A-500 (5.0 x 10 2 ), A-1000(1.01×10 3 ), A-2500(2.63×10 3 ), A-5000(5.97×10 3 ), F-1(1.02×10 4 ), F-2(1.81×10 4 ), F-4(3.97×10 4 ), F-10(9.64×10 4 ), F-20(1.90×10 5 ), F-40(4.27×10 5 ), F-80(7.06×10 5 ), F-128(1.09×10 6 )) was used as a standard sample. The numbers in parentheses indicate the molecular weight. Measuring device: HLC-8220GPC (Tosoh Corporation) Analytical column: TSKgel GMHXL + TSKgel G3000HXL (manufactured by Tosoh Corporation)

[0103] [Melting point of release agent] Using a differential scanning calorimeter "DSC Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C at a heating rate of 10°C / min, and cooled to -10°C at a heating rate of 5°C / min. The sample is then heated to 180°C at a heating rate of 10°C / min and measured. The maximum endothermic peak temperature observed in the melting endothermic curve obtained is taken as the melting point of the wax.

[0104] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.

[0105] [Volume Median Particle Size of Toner] Measuring device: Coulter Multisizer II (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: Coulter Multisizer AccuComp version 1.19 (Beckman Coulter, Inc.) Electrolyte: Isoton II (Beckman Coulter, Inc.) Dispersion liquid: Emulgen 109P (Kao Corporation, polyoxyethylene lauryl ether, HLB (Griffin): 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of the electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte so that the particle size of 30,000 particles could be measured in 20 seconds. 30,000 particles were measured, and the volume median particle size (D 50 ) is required.

[0106] Resin manufacturing example 1 The raw material monomers shown in Table 1 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. Then, an esterification catalyst and an esterification promoter were added, and the temperature was raised to 210°C over 1 hour, and the reaction was continued at 8.0 kPa until the softening point shown in Table 1 was reached, to obtain crystalline polyester resins (resins C1 to C8).

[0107] [Table 1]

[0108] Resin manufacturing example 2 The raw material monomers other than adipic acid, the esterification catalyst and the esterification promoter shown in Table 2 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235° C. under a nitrogen atmosphere, and polycondensation was carried out at 235° C. for 6 hours. The temperature was then lowered to 210° C., and adipic acid was added, and the reaction was carried out at 210° C. for 2 hours, and then the reaction was continued at 210° C. under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, to obtain amorphous polyester resins (resins AL1 and AL2).

[0109] Resin manufacturing example 3 The raw material monomers other than adipic acid and trimellitic anhydride, the esterification catalyst and the esterification promoter shown in Table 2 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the temperature was raised to 235°C under a nitrogen atmosphere, and polycondensation was carried out at 235°C for 6 hours. Thereafter, the temperature was lowered to 210°C, and adipic acid and trimellitic anhydride were added, and the reaction was carried out at 210°C for 2 hours, and then the reaction was carried out at 210°C under a reduced pressure of 10 kPa until the softening point shown in Table 2 was reached, to obtain an amorphous polyester resin (resin AH1).

[0110] [Table 2]

[0111] Examples 1 to 6 and Comparative Examples 1 to 3 As the binder resin, 15 parts by mass of resin C, 55 parts by mass of resin AL, and 30 parts by mass of resin AH shown in Table 3 were used, and 5 parts by mass of colorant "ECB-301" (manufactured by Dainichi Seikagaku Kogyo Co., Ltd., copper phthalocyanine pigment), 1 part by mass of charge control agent "LR-147" (manufactured by Nippon Carlit Co., Ltd.), and 2 parts by mass of release agent "HNP-9" (manufactured by Nippon Seiro Co., Ltd., paraffin wax, melting point: 75°C) were thoroughly stirred with a Henschel mixer, and then melt-kneaded using a co-rotating twin-screw extruder with a total length of 1560 mm, a screw diameter of 42 mm, and a barrel inner diameter of 43 mm. The screw rotation speed was 200 r / min, the heating setting temperature in the screw was 90°C, the temperature of the kneaded material was 140°C, the feed rate of the kneaded material was 10 kg / h, and the average residence time was about 18 seconds. The obtained kneaded product was cooled from 140°C to 50°C in 1.5 hours, rolled and cooled at 50°C with a cooling roller, pulverized in a jet mill, classified, and the volume median particle size (D 50 ) Toner particles of 5.5 μm were obtained.

[0112] To 100 parts by mass of the obtained toner particles, 1.5 parts by mass of "Aerosil R-972" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of "RY-50" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) were added as external additives, and the mixture was mixed for 5 minutes at 3600 r / min using a Henschel mixer to perform external additive treatment and obtain a toner.

[0113] Test Example 1 [Abrasion resistance] A halftone image (2 dots 2 spaces halftone image) consisting of 2 dots of printed areas (points) and 2 dots of non-printed areas (blanks) was printed at a resolution of 600 dpi on coated paper "OK ​​Topcoat+" (Oji Paper Co., Ltd.) using a commercially available printer "Microline (registered trademark) 5400" (Oki Data Co., Ltd.). The resulting print was applied to a cellulose nonwoven fabric "Bencotto M3-II" (Asahi Kasei Co., Ltd.) with a load of 2 kg (contact area 900 mm2). 2The reflective image density of the printed matter before and after rubbing was measured using a colorimeter "SpectroEye" (GretagMacbeth, light irradiation conditions: standard light source D 50 The measurements were made using a 2° observation field, density standard DINNB, and absolute white standard. The average of the values ​​measured at three arbitrary points on each image was taken as the image density, and the amount of change in image density before and after rubbing [(image density before rubbing - image density after rubbing)] was calculated. The results are shown in Table 3. The smaller the amount of change in image density before and after rubbing, the better the abrasion resistance.

[0114] Test Example 2 [Crushability] In the toner manufacturing process, 1 kg of the molten kneaded material (approximately 3 cm square plate piece) was collected and put into a Rotoplex (manufactured by Hosokawa Micron Corporation, model R20 / 10) equipped with a screen with a mesh size of 3 mm, and pulverized. The pulverized molten kneaded material was classified into particles with a particle size of 710 μm or more and 1000 μm or less using wire mesh sieves (manufactured by Iida Manufacturing Co., Ltd.) with mesh sizes of 1000 μm and 710 μm specified in JIS Z 8801-1:2000. 20 g of the classified particles were pulverized for 10 seconds with a coffee mill (manufactured by PHILIPS, HR-2170 type), and then passed through a 150 μm sieve, and the weight A (g) of the toner that passed through was precisely weighed. The pulverizability was calculated from the weighed weight using the following formula, and this operation was performed three times to obtain the average value. The results are shown in Table 3. The higher the value, the better the pulverizability. Grindability (%) = (A [g] / 20.0 [g]) x 100

[0115] Test Example 3 [Glossiness] The toner was mounted on a copy machine "AR-505" (manufactured by Sharp Corporation) whose fixing unit was modified to enable fixing outside the machine, and a printout was obtained in an unfixed state (print area: 2 cm × 12 cm, adhesion amount: 0.3 mg / cm 2). Thereafter, a fixing machine (fixing speed 300 mm / sec) adjusted to a total fixing pressure of 40 kgf was used, and the temperature of the fixing roll was set to the minimum fixing temperature + 20°C to fix the unfixed printed matter. The paper used for printing was coated paper "OK ​​Topcoat+" (manufactured by Oji Paper Co., Ltd.). After leaving the resulting printed matter at a temperature of 45°C for one day, the gloss was measured using a gloss meter "IG-330" (manufactured by Horiba, Ltd.) with cardboard placed under the image and the light irradiation condition set at 60°. The results are shown in Table 3. The higher the value obtained, the higher the gloss.

[0116] [Table 3]

[0117] From the above results, it can be seen that the toners of Examples 1 to 6 have good grindability during the production process and are also excellent in abrasion resistance and gloss, compared to Comparative Examples 1 and 3, which contain crystalline polyester resins using monocarboxylic acids with short carbon chains as the aliphatic monocarboxylic acid compound, and Comparative Example 2, which contains a crystalline polyester resin in which the amount of an aliphatic monocarboxylic acid compound used is too small. In particular, a comparison between Example 1 and Example 6 reveals that when the content of the propylene oxide adduct of bisphenol A in the alcohol component of the amorphous polyester resin is high, the improvement in grindability is remarkable. [Industrial Applicability]

[0118] The toner for developing electrostatic images containing the binder resin composition for toners of the present invention is suitably used for developing latent images formed in electrostatic image developing methods, electrostatic recording methods, electrostatic printing methods and the like.

Claims

1. A binder resin composition for toner, comprising a crystalline polyester resin and an amorphous polyester resin, wherein the crystalline polyester resin is a polycondensate of raw material monomers including ethylene glycol, an aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms, and an aliphatic monocarboxylic acid compound having 16 to 24 carbon atoms, and the content of the aliphatic monocarboxylic acid compound in the raw material monomers is 7 mol % or more and 20 mol % or less.

2. 2. The binder resin composition for toner according to claim 1, wherein the aliphatic dicarboxylic acid compound having 12 to 16 carbon atoms is dodecanedioic acid and / or tetradecanedioic acid.

3. 3. The binder resin composition for toner according to claim 1, wherein the aliphatic monocarboxylic acid compound having 16 to 24 carbon atoms is stearic acid and / or behenic acid.

4. 4. The binder resin composition for toner according to claim 1, wherein the sum of the acid value and the hydroxyl value of the crystalline polyester resin is 15 mgKOH / g or less.

5. 5. The binder resin composition for toner according to claim 1, wherein the weight average molecular weight of the crystalline polyester resin is 5,000 or more and 12,000 or less.

6. 6. The binder resin composition for toner according to claim 1, wherein the amorphous polyester resin comprises an amorphous polyester resin AL having a weight average molecular weight of 4,000 or more and 10,000 or less, and the binder resin composition contains the amorphous polyester resin AL in an amount of 40% by mass or more.

7. 7. A toner for developing electrostatic images, comprising the binder resin composition for toners according to claim 1 and a colorant.

Citation Information

Patent Citations

  • Toner binder resin composition

    JP2016090628A

  • Method for producing electrophotographic toner

    JP2019095475A

  • Method for manufacturing toner for electrostatic charge image development

    JP2020060687A

  • Toner

    JP2021043397A

  • Binder resin composition for toner

    JP2021076800A